Preisstrategien im deutschen Lebensmitteleinzelhandel: Eine empirische Analyse; Pricing patterns and promotion activities in the German grocery retail industry - Anke Mos̈er (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2001)
– The present article discusses several pricing patterns and promotion activities in the German grocery retail industry. Special sales offers on the one hand and continuous pricing on the other hand affect the price instability of several selected products. Altogether the grocery retail industry exerts a stabilizing effect on prices in comparison with the price instability of agricultural commodities in the world market. Different price levels for products in some retail outlets show that a mixed price calculation is used. Price elasticities in the elastic part of the demand function for four selected products indicate that consumers react strongly to price discounts at the point of sale. Beside pricing strategies, different promotion activities affect demand for individual products strongly.
Keywords: 330; Lebensmittelhandel; Preismanagement; Deutschland